REQUIREMENTS THAT HAVE TO BE OWNED BY THE FLIGHT COMPANY IF PASSING THEIR ARMY ACCORDING TO INDONESIAN AIR LAWS - Evert Maximiliaan Tentua (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Every airline that flies its fleet in Indonesian airspace must meet several requirements, such as nationality mark and registration number and have obtained diplomatic clearance. security clearance or flight approval.